Energy aware detection and prevention of black hole attack in MANET - Panda, Niranjan; Kumar Pattanayak, Binod (International Journal of Engineering and Technology, 2018)
Energy and security are the two vital components of Mobile Ad-hoc Networks (MANETs). During routing finding an optimal path from sender to receiver sense of path length (number of hops), longevity (battery life) and security becomes an essential requirement. Variety of schemes are proposed by the researchers for finding the shortest path along with energy saving and protecting from attacks Black-hole and gray-hole attacks are some of the most harmful attacks against MANET communication and needs attention. These attacks may cause by insider or outsider malicious node(s) who may drop packets or misroute the information during communication from sender node to receiver node. In our study we proposed an intelligent routing protocol based on Ant Colony Optimization (ACO) technique that finds shortest path from source to destination, applies the concept of power aware techniques to save energy increasing the longevity of the link avoiding link failure and also uses the concept of digital signatures, watchdog and path rater for detection and avoidance ofblack-hole and gray-hole attacks. Simulation study of the proposed scheme is made over some network parameters and found to be efficient in comparison to the basic AODV routing protocol.